Parents' Views on YouTube in Early Childhood Education - Nadya Putri Pertiwi; Sri Widayati; Aziizah Retno Sulistyani (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
In this digital era, the internet has become a basic need for everyone globally. Not only adults, but early childhood also often use the internet to find entertainment. One of the applications that children often use to find entertainment is YouTube. There are various kinds of content on YouTube, including movies, gaming videos, educational videos, vlogs, etc. So that parents or teachers also use YouTube as a learning medium for children. This is what attracted the attention of researchers to identify and describe the reason parents give YouTube videos to their children. The purpose of this study is to determine parents’ views on YouTube and relate them to early childhood education. This research was quantitative research using the survey method. The research instrument used is a questionnaire delivered via Google Forms. In this study, it was found that parents have given YouTube access to their children at an early age by the reason to stimulate children's development. Through mobile phones, children were introduced to and started to actively access YouTube content such as children's songs almost every day. On the other hand, parents also recognized that they found side effects on their children being YouTube users. Moreover, there were still parents who are not aware on accompany their children when accessing various YouTube content. Appropriate YouTube content can have a good impact on children's growth and development, such as being able to communicate well, being active, knowing religious values, and imitating good character figures. But keep in mind that parents must always accompany their children and direct them to watch YouTube according to their needs.